Quantifying uncertainty for AWARE characterization factors - Anne‐Marie Boulay; Pascal Lesage; Ben Amor; Stephan Pfister (Journal of Industrial Ecology, 2021)

Influence of infrastructure material composition and microtopography on marine biofilm growth and photobiology - Baptiste Vivier; Pascal Claquin; Christophe Lelong; Quentin Lesage; Mathias Peccate; Bastien Hamel; Marine Georges; Amel Bourguiba; Nassim Sebaibi; Mohamed Boutouil; Didier Goux; Jean-Claude Dauvin; et al. (Biofouling, 2021)

Prioritizing regionalization efforts in life cycle assessment through global sensitivity analysis: a sector meta-analysis based on ecoinvent v3 - Laure Patouillard; Pierre Collet; Pascal Lesage; Pablo Tirado Seco; Cécile Bulle; Manuele Margni (The International Journal of Life Cycle Assessment, 2019)

Are there infinitely many trucks in the technosphere, or exactly one? How independent sampling of instances of unit processes affects uncertainty analysis in LCA - Pascal Lesage; Chris Mutel; Urs Schenker; Manuele Margni (The International Journal of Life Cycle Assessment, 2019)

Uncertainty analysis in LCA using precalculated aggregated datasets - Pascal Lesage; Chris Mutel; Urs Schenker; Manuele Margni (The International Journal of Life Cycle Assessment, 2018)

Effects of Distribution Choice on the Modeling of Life Cycle Inventory Uncertainty: An Assessment on the Ecoinvent v2.2 Database - Stéphanie Muller; Christopher Mutel; Pascal Lesage; Réjean Samson (Journal of Industrial Ecology, 2018)
Summary Life cycle inventory data have multiple sources of uncertainty. These data uncertainties are often modeled using probability density functions, and in the ecoinvent database the lognormal distribution is used by default to model exchange uncertainty values. The aim of this article is to systematically measure the effect of this default distribution by changing from the lognormal to several other distribution functions and examining how this change affects the uncertainty of life cycle assessment results. Using the ecoinvent 2.2 inventory database, data uncertainty distributions are switched from the lognormal distribution to the normal, triangular, and gamma distributions. The effect of the distribution switching is assessed for both impact assessment results of individual products system, as well as comparisons between product systems. Impact assessment results are generated using 5,000 Monte Carlo iterations for each product system, using the Intergovernmental Panel on Climate Change (IPCC) 2001 (100‐year time frame) method. When comparing the lognormal distribution to the alternative default distributions, the difference in the resulting median and standard deviation values range from slight to significant, depending on the distributions used by default. However, the switch shows practically no effect on product system comparisons. Yet, impact assessment results are sensitive to how the data uncertainties are defined. In this article, we followed what we believe to be ecoinvent standard practice and preserved the “most representative” value. Practitioners should recognize that the most representative value can depart from the average of a probability distribution. Consistent default distribution choices are necessary when performing product system comparisons.

The application of the pedigree approach to the distributions foreseen in ecoinvent v3 - Stéphanie Muller; Pascal Lesage; Andreas Ciroth; Christopher Mutel; Bo P. Weidema; Réjean Samson (The International Journal of Life Cycle Assessment, 2016)

Empirically based uncertainty factors for the pedigree matrix in ecoinvent - Andreas Ciroth; Stéphanie Muller; Bo Weidema; Pascal Lesage (The International Journal of Life Cycle Assessment, 2016)

The Quebec Life Cycle Inventory Database Project - Pascal Lesage; Réjean Samson (The International Journal of Life Cycle Assessment, 2016)

Giving a scientific basis for uncertainty factors used in global life cycle inventory databases: an algorithm to update factors using new information - Stéphanie Muller; Pascal Lesage; Réjean Samson (The International Journal of Life Cycle Assessment, 2016)

Temporal differentiation of background systems in LCA: relevance of adding temporal information in LCI databases - Ariane Pinsonnault; Pascal Lesage; Annie Levasseur; Réjean Samson (The International Journal of Life Cycle Assessment, 2014)

Declaration of concern—an unambiguous rebuttal of the LEO-SCS-002 draft standard - Christoph Koffler; Jon Dettling; Cashion East; Matthias Finkbeiner; Sergio F. Galeano; Roland Geyer; Mark J. Goedkoop; Troy R. Hawkins; Connie D. Hensler; Arpad Horvath; Sebastien Humbert; Scott M. Kaufman; et al. (The International Journal of Life Cycle Assessment, 2013)

Biogenic Carbon and Temporary Storage Addressed with Dynamic Life Cycle Assessment - Annie Levasseur; Pascal Lesage; Manuele Margni; Réjean Samson (Journal of Industrial Ecology, 2013)
Summary A growing tendency in policy making and carbon footprint estimation gives value to temporary carbon storage in biomass products or to delayed greenhouse gas (GHG) emissions. Some life cycle‐based methods, such as the British publicly available specification (PAS) 2050 or the recently published European Commission's International Reference Life Cycle Data System (ILCD) Handbook , address this issue. This article shows the importance of consistent consideration of biogenic carbon and timing of GHG emissions in life cycle assessment (LCA) and carbon footprint analysis. We use a fictitious case study assessing the life cycle of a wooden chair for four end‐of‐life scenarios to compare different approaches: traditional LCA with and without consideration of biogenic carbon, the PAS 2050 and ILCD Handbook methods, and a dynamic LCA approach. Reliable results require accounting for the timing of every GHG emission, including biogenic carbon flows, as soon as a benefit is given for temporarily storing carbon or delaying GHG emissions. The conclusions of a comparative LCA can change depending on the time horizon chosen for the analysis. The dynamic LCA approach allows for a consistent assessment of the impact, through time, of all GHG emissions (positive) and sequestration (negative). The dynamic LCA is also a valuable approach for decision makers who have to understand the sensitivity of the conclusions to the chosen time horizon.

Assessing temporary carbon sequestration and storage projects through land use, land-use change and forestry: comparison of dynamic life cycle assessment with ton-year approaches - Annie Levasseur; Pascal Lesage; Manuele Margni; Miguel Brandão; Réjean Samson (Climatic Change, 2012)

Systematic disaggregation: a hybrid LCI computation algorithm enhancing interpretation phase in LCA - Guillaume Bourgault; Pascal Lesage; Réjean Samson (The International Journal of Life Cycle Assessment, 2012)

Life Cycle Attribute Assessment - Evan Andrews; Pascal Lesage; Catherine Benoît; Julie Parent; Gregory Norris; Jean‐Pierre Revéret (Journal of Industrial Ecology, 2009)
Summary Practitioners of life cycle assessment (LCA) have recently turned their attention to social issues in the supply chain. The United Nations life cycle initiative's social LCA task force has completed its guidelines for social life cycle assessment of products, and awareness of managing upstream corporate social responsibility (CSR) issues has risen due to the growing popularity of LCA. This article explores one approach to assessing social issues in the supply chain—life cycle attribute assessment (LCAA). The approach was originally proposed by Gregory Norris in 2006, and we present here a case study. LCAA builds on the theoretical structure of environmental LCA to construct a supply chain model. Instead of calculating quantitative impacts, however, it asks the question “What percentage of my supply chain has attribute X?” X may represent a certification from a CSR body or a self‐defined attribute, such as “is locally produced.” We believe LCAA may serve as an aid to discussions of how current and popular CSR indicators may be integrated into a supply chain model. The case study demonstrates the structure of LCAA, which is very similar to that of traditional environmental LCA. A labor hours data set was developed as a satellite matrix to determine number of worker hours in a greenhouse tomato supply. Data from the Quebec tomato producer were used to analyze how the company performed on eight sample LCAA indicators, and conclusions were drawn about where the company should focus CSR efforts.

Environmental assessment of brownfield rehabilitation using two different life cycle inventory models - Pascal Lesage; Tomas Ekvall; Louise Deschênes; Réjean Samson (The International Journal of Life Cycle Assessment, 2007)

Environmental assessment of brownfield rehabilitation using two different life cycle inventory models - Pascal Lesage; Tomas Ekvall; Louise Deschênes; Réjean Samson (The International Journal of Life Cycle Assessment, 2007)

Environmental assessment of brownfield rehabilitation using two different life cycle inventory models - Pascal Lesage; Tomas Ekvall; Louise Deschênes; Réjean Samoson (The International Journal of Life Cycle Assessment, 2007)

Environmental assessment of brownfield rehabilitation using two different life cycle inventory models - Pascal Lesage; Tomas Ekvall; Louise Deschênes; Réjean Samoson (The International Journal of Life Cycle Assessment, 2007)

Evaluating Holistic Environmental Consequences of Brownfield Management Options Using Consequential Life Cycle Assessment for Different Perspectives - Pascal Lesage; Louise Deschênes; Réjean Samson (Environmental Management, 2007)

Comparative life cycle assessment of two landfill technologies for the treatment of municipal solid waste - Jean-François Ménard; Pascal Lesage; Louise Deschênes; Réjean Samson (The International Journal of Life Cycle Assessment, 2004)